Spirituality and Resilience in Involuntary Childlessness: A Correlational Study - Ryvo Immanuel; Ratriana Y.E Kusumiati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Involuntary childlessness is a condition of not having children due to external factors, such as illness or other things that are beyond individuals’ control, which make them unable to have children. Involuntary childless couples have challenges in psychological, emotional, and social aspects. This study aims to determine the relationship between spirituality and resilience in involuntary childless families. This study used a quantitative method with a correlational design. There were 187 participants in this study, consisting of 80 husbands and 107 wives of childless individuals. The research data is collected from involuntary childless families using a snowball sampling. Spirituality was measured by the Spiritual Attitude and Involvement List (α=0.995), and resilience was measured by the Connor Davidson Resilience Scale (α=0.977). The results showed a sig=0.000 (p<0.005) and a correlation coefficient of 0.463, where the higher the level of spirituality, the higher the resilience in involuntary childless families. Involuntary childless families can increase their spirituality and be more resilient to the problems faced by following spirituality and non-spirituality practices. Keywords: spirituality, resilience, involuntary childless family, mental health